2013
DOI: 10.1001/jama.2013.4135
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Perioperative β-Blockade With Mortality and Cardiovascular Morbidity Following Major Noncardiac Surgery

Abstract: ImportanceThe effectiveness of perioperative ␤-blockade in patients undergoing noncardiac surgery remains controversial.Objective To determine the associations of early perioperative exposure to ␤-blockers with 30-day postoperative outcome in patients undergoing noncardiac surgery. Design, Setting, and PatientsA retrospective cohort analysis evaluating exposure to ␤-blockers on the day of or following major noncardiac surgery among a populationbased sample of 136 745 patients who were 1:1 matched on propensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(77 citation statements)
references
References 43 publications
(46 reference statements)
0
69
0
6
Order By: Relevance
“…A recent large retrospective analysis of the Veterans Affairs Medical Center surgical database also failed to find diabetes as a significant predictor of cardiac outcomes. 19 Focused attempts to include modified terms related to diabetes mellitus or preoperative blood sugar levels could not significantly improve the ability to predict the risk of MCCs or improve the accuracy or the discrimination of the index. Glycosylated hemoglobin has been advocated as an important risk factor in diabetic outcomes and may be a factor that could potentially improve the index; [20][21][22] however, the data in our database were insufficient to assess this variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large retrospective analysis of the Veterans Affairs Medical Center surgical database also failed to find diabetes as a significant predictor of cardiac outcomes. 19 Focused attempts to include modified terms related to diabetes mellitus or preoperative blood sugar levels could not significantly improve the ability to predict the risk of MCCs or improve the accuracy or the discrimination of the index. Glycosylated hemoglobin has been advocated as an important risk factor in diabetic outcomes and may be a factor that could potentially improve the index; [20][21][22] however, the data in our database were insufficient to assess this variable.…”
Section: Discussionmentioning
confidence: 99%
“…This definition does have the advantage of being the threshold for chronic kidney disease as defined by the National Kidney Foundation. 19 On the basis of these considerations, we would advocate for a 5-Factor model where the renal component is denoted by a low GFR and diabetes is dropped from the index.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was observed in vascular surgery. The overall rate of stroke was higher in the beta-blocker group (8).…”
Section: Time Of Initiationmentioning
confidence: 79%
“…Metoprolol was more frequently prescribed but the mortality rate was significantly higher in the metoprolol group compared to the atenolol group. The rate of stroke was also significantly higher in the metoprolol group (8). In 2016, Cohn noted that more cardioselective beta-blockers (atenolol or bisoprolol) had more beneficial effects than metoprolol did, and metoprolol had no beneficial effects in diabetic patients and in vascular surgery (27).…”
Section: Type Of Beta-blockermentioning
confidence: 99%
“…For example, prior observational studies have suggested that perioperative beta blockers are associated with benefit in patients at higher predicted cardiac risk, while they are associated with harm in individuals at lower predicted cardiac risk. 2,3 Fourth, risk information can help specify the required intensity of perioperative monitoring, such as whether a patient warrants invasive monitoring or postoperative care in a critical care unit. The role of estimated perioperative risk in rationally choosing postoperative care settings is especially important since monitored acute care beds are expensive and often scarce resources.…”
Section: Résumémentioning
confidence: 99%